Para leer la Filosofía del Derecho de Hegel - De Zan, Julio (ARFIL y UNL, 2018)
The beginning of Philosophy of Right with the concept of “Abstract Right” and “morality” presents the appearance of a form of treatment typical of the methodological individualism of natural right theories. Nevertheless, Hegel makes it clear that the expository plan does not reflect the genetic, temporal or ontological structure of the issue. This article will thus try to give an answer to the question about the criteria to which this problematic structure of the work plan responds. The thesis sustained by the author is that the first two parts of the work have to be read mainly as a critical-negative exposition of the current theories, and only the third part about the institutions of Sittlichkeit provides a positive exposition of Hegel’s thought. The treatment of Right and morality is not merely negative either, but takes up again and at the same time conforms to Kant’s and Natural Rights fundamental principles, as necessary conditions for the comprehension of the institutions of modern society and modern State.